The Complete Spitzer Survey of Stellar Structure in Galaxies (CS4G) - Sanchez-Alarcón, P. M.; Salo, H.; Knapen, J. H.; Comerón, S.; Román, J.; Watkins, A. E.; Buta, R. J.; Laine, S.; Falcón-Ramirez, J. M.; Anetjärvi, M.; Athanassoula, E.; Bosma, A.; et al. (EDP SCIENCES S A, 2025)
Context. The Spitzer Survey of Stellar Structure in Galaxies (S4G), together with its Early Type Galaxy (ETG) extension, stands as the most extensive dataset of deep uniform mid-infrared (mid-IR; 3.6 and 4.5 μm) imaging for a sample of 2817 nearby (d < 40 Mpc) galaxies. However, the velocity criterion used to select the original sample results in an additional 422 galaxies without H I detection that should have been included in the S4G on the basis of their optical recession velocities.
Aims. In order to create a complete magnitude-, size-, and volume-limited sample of nearby galaxies, we collected 3.6 μm and i-band images using archival data from different surveys and complemented it with new observations for the missing galaxies. Since most, but not all, of these galaxies have a Hubble type in Hyperleda THL > 0, we denote the sample of these additional galaxies as disc galaxy (DG) extension. We present the Complete Spitzer Survey of Stellar Structure in Galaxies (CS4G), encompassing a sample of 3239 galaxies (S4G+ETG+DG) with consistent imaging, surface brightness profiles, photometric parameters, and revised morphological classification.
Methods. Following the original strategy of the S4G survey, we produced masks, surface brightness profiles, and curves of growth using masked 3.6 μm and i-band images. From these profiles, we derived the integrated quantities, including total magnitude, stellar mass, concentration parameter, and galaxy size, converting between optical i-band and 3.6 μm. We also re-measured these parameters for the S4G and ETG to create a homogenous sample. We present new morphologically revised T-types, and we showcase mid-IR scaling relations for the stellar mass, galaxy size, concentration index, and morphological type.
Results. Our new masking procedure increases the number of pixels masked out by a factor of five, improving the masking of fainter regions over previous S4G data. Our photometric parameters from i-band imaging yield measurements consistent with the original sample (S4G) and its ETG extension in the 3.6 μm band. The new DG extension consists of galaxies with a wide morphological range (−5 < THL < 10) and a mass range of 6 < log(M⋆/M⊙) < 11. The galaxies in the DG sample have an average mass of log(M⋆/M⊙) = 9.21, an average galaxy isophotal radius at 25.5 mag arcsec−2 of R25.5 = 7.1 kpc, and an average concentration index of C82 = 2.92.
Conclusions. We completed the S4G sample by incorporating 422 galaxies into the original dataset. The new galaxies constitute 15% of the total previous sample (S4G+ETG), but in the lower-mass range (M⋆ < 109 M⊙), and the disc galaxy extension increases the sample by 36%. The CS4G includes at least 99.94% of the complete sample of nearby galaxies, meeting the original selection criteria based on a comparison with the NED database. We make the images and surface brightness profiles available to the community together with the conjunct catalogue of the whole CS4G dataset with consistent photometric measurements for 3239 galaxies. The CS4G will enable a wide set of investigations into galaxy structure and evolution, and it will complement the optical, near-IR, and mid-IR imaging that will obtained in the coming years with Euclid, Rubin, Roman, and other research projects.